1997
DOI: 10.1159/000006737
|View full text |Cite
|
Sign up to set email alerts
|

Does Heart Rate Variability Change in Angina Pectoris Patients Treated with Spinal Cord Stimulation?

Abstract: To determine whether spinal cord stimulation has any effect on the autonomic nervous tone of the heart, heart rate variability was used as an indicator of autonomic nervous control of the heart. The components time domain and power spectral analyses of heart rate variability were measured in 21 patients with angina pectoris. Twenty-four-hour Holter recordings were obtained before and after 12 months with spinal cord stimulation. No significant attenuation of time domain or spectral components of heart rate var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In accordance with previous investigations, we found no significant change in heart rate variability after spinal cord stimulation [12, 13], but our study was performed without ongoing stimulation. The results indicate that there are no long-term or acute effects of spinal cord stimulation on cardiac autonomic activity as measured by heart rate variability.…”
Section: Effects Of Intervention On Heart Rate Variabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous investigations, we found no significant change in heart rate variability after spinal cord stimulation [12, 13], but our study was performed without ongoing stimulation. The results indicate that there are no long-term or acute effects of spinal cord stimulation on cardiac autonomic activity as measured by heart rate variability.…”
Section: Effects Of Intervention On Heart Rate Variabilitysupporting
confidence: 93%
“…Heart rate variability analysis is a method to study cardiac autonomic neural regulation. Two recent studies concerning the effects of spinal cord stimulation on heart rate variability showed no effects of the treatment on the autonomic nervous system detectable by heart rate variability analysis [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous literature assessed this issue, hitherto with contradictory results. Andersen 17 and Hautvast et al 18 investigated the relationship between SCS and HRV, respectively, on 48‐ and 24‐hour ECG recordings, activating the SCS only for a minority of the postimplant recording periods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct sympatholytic mechanisms, previous work has shown that SCS enhances vagal tone. 15,24,25 This may be important because in HF an upregulation of inflammatory signaling occurs, 26 and vagal nerve activation has been linked to attenuation of inflammatory responses. 27,28 Finally, in other types of experimental canine models, vagal nerve stimulation has decreased the incidence of sudden cardiac death such as in post-MI exercising canines, 29 and has improved ventricular function in a canine HF model produced by repeated coronary …”
Section: Potential Mechanismsmentioning
confidence: 99%